Current Options for the Treatment of Pectus Carinatum: When to Brace and When to Operate? - Emil, Sherif (European Journal of Pediatric Surgery, 2018)
Pectus carinatum has traditionally been described as a rare chest wall anomaly in comparison to pectus excavatum. However, recent data from chest wall anomaly clinics demonstrate that this deformity is probably much more frequent than once believed. In the past, invasive surgical correction by the Ravitch technique was essentially the only option for treatment of pectus carinatum. Major advances over the past two decades have provided additional options, including noninvasive chest wall bracing and minimally invasive surgical correction. This article will discuss current options for the treatment of pectus carinatum, and some of the factors that should be taken into account when choosing the options available. Diagnosis and treatment of the pectus arcuatum variant will also be described.
Keywords: pectus carinatum; arcuatum; bracing; surgical correction; treatment; outcomes